The Effectiveness of Edmodo- Based Project Based Learning on Students HOTS - Albadri Albadri; Suyahman Suyahman; Sutarto Sutarto; Normansyah Normansyah; Ranat Mulia Pardede; Mohammad Edy Nurtamam; Tomi Apra Santosa (Universitas Muhammadiyah Enrekang, 2024)
Abstract The 21st century has a significant impact on the development of education. 21st century education directs students to have higher order thinking skills (HOTS). Furthermore, project-based learning is one of the learning models that is highly recommended to encourage students' HOTS skills. Many applications of project-based learning models have not found the effect of edmodo-based project-based learning on students' HOTS skills. This study aims to determine the effect of edmodo-based project-based learning model on students' Higher Order Thinking Skills (HOTS). This type of research is a meta-analysis. The data source comes from the analysis of 10 national journals indexed by SINTA. Data sources were searched through Researcgate, Google Scholar, DOAJ and Mendeley. Inclusion criteria are that the research comes from SINTA indexed journals, the research must be experimental, the research was published in 2021-2023 and reports complete data for calculating effect size. Statistical analysis using JASP assistance. The results concluded that the edmodo-based project-based learning model had a significant effect on students' HOTS with an average effect size of 1.097 with high effect size criteria. This finding explains that the edmodo-based project-based learning model is effective in improving students' higher order thinking skills (HOTS) with a z value = 6.474; P < 0.001